2020
DOI: 10.1093/fampra/cmaa083
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations and socio-economic disparities in neonatal mortality in Angola: a cross-sectional study using demographic and health surveys

Abstract: Background Inequalities in neonatal mortality rates (NMRs) in low- and middle-income countries show key disparities at the detriment of disadvantaged population subgroups. There is a lack of scholarly evidence on the extent and reasons for the inequalities in NMRs in Angola. Objective The aim of this study was to assess the socio-economic, place of residence, region and gender inequalities in the NMRs in Angola. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
5
3
0
Order By: Relevance
“…Pro-rich inequalities in SBA in Guinea are consistent with previous studies in Bangladesh [ 44 46 ]. Gender-based variations of NMR observed in Guinea were comparable with prior studies in Burundi and Angola [ 31 , 47 ]. Possible reasons could be due to inability to afford costs related to childbirth among households with lower socio-economic status [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Pro-rich inequalities in SBA in Guinea are consistent with previous studies in Bangladesh [ 44 46 ]. Gender-based variations of NMR observed in Guinea were comparable with prior studies in Burundi and Angola [ 31 , 47 ]. Possible reasons could be due to inability to afford costs related to childbirth among households with lower socio-economic status [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…Profound pro-urban inequalities in SBA and NMR are comparable with prior studies in Angola and Burundi [ 31 , 47 ]. Urban-rural differences in SBA have been reported in previous studies in Ethiopia and Bangladesh [ 46 , 51 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The WHO recommends spacing childbirths at least 24-36 months apart (16). Moreover, previous studies conducted in Angola (17), Uganda(18) and LMICs (19) have shown that place of residence, maternal age at rst birth, birth weight, household wealth index, and maternal education were all signi cantly associated with neonatal mortality.…”
Section: Introductionmentioning
confidence: 83%
“…The WHO recommends spacing childbirths at least 24-36 months apart [16]. Moreover, previous studies conducted in Angola [17], Uganda [18] and other LMICs [19] have shown that place of residence, maternal age at first birth, birth weight, household wealth index, and maternal education were all significantly associated with neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%